A Randomized, Open Label, Exploratory Trial Comparing Efficacy of Amantadine and Ropinirole in Restless Legs Syndrome - Madhaw, Govind; Gupta, Ravi; Dhamija, Puneet; Kumar, Niraj (Sleep Science, 2023)
Objective Amantadine has both anti-glutamatergic and dopaminergic action and may improve restless legs syndrome (RLS). We compared the efficacy and adverse-effect profile of amantadine and ropinirole in RLS.Methods In this randomized, open-label, 12-week flexible-dose exploratory study, RLS patients with international RLS study group severity scale score (IRLSS) > 10 were randomized to receive either amantadine(100-300mg/day) or ropinirole (0.5-2mg/day). Drug dose was increased until week-6 if IRLSS failed to improve by ≥10% of previous visit score. IRLSS change from baseline at week-12 was the primary outcome. Secondary outcomes included change in RLS-related quality of life (RLS-QOL) and insomnia severity index (ISI), along with clinical-global-impression of change/improvement (CGI-I), and proportion of patients with adverse-effects and resulting discontinuation.Results Twenty-four patients received amantadine and 22 received ropinirole. Both groups had a significant effect for visit*treatment arm (F (2.19,68.15) =4.35;P = 0.01). With a similar baseline IRLSS, both intention-to-treat (ITT) and per-protocol analyses revealed comparable IRLSS until week-8, with ropinirole appearing superior from week-10 to week-12 (week-12 IRLSS, amantadine vs ropinirole:17.0 ±  5.7 vs 9.0 ±  4.4;P < 0.001). ITT analysis at week-12 showed comparable proportion of responders (≥10% IRLSS reduction) in both groups (P = 0.10). Both drugs improved sleep and QOL, but week-12 scores favoured ropinirole [(ISI:14.4 ±  5.7 vs 9.4 ±  4.5; P = 0.001) ;(RLS-QOL:70.4 ±  17.9 vs 86.5 ±  9.8; P = 0.005)]. CGI-I at week-12 favoured ropinirole (Mann-Whitney U = 35.50, S. E = 23.05;P = 0.01). Four patients in amantadine and two in ropinirole group developed adverse effects, with resulting discontinuation in two patients on amantadine.Conclusions The present study reports equivalent reduction in RLS symptoms with both amantadine and ropinirole until week-8, with the latter being superior from week-10 onwards. Ropinirole was better tolerated.
Keywords: Restless legs syndrome; Amantadine; Dopamine agonists; Ropinirole; N-Methyl-D-Aspartic acid; Insomnia